2014
DOI: 10.5455/2320-6012.ijrms20141175
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of serum lipid profile between prehypertensive and normotensive

Abstract: Background: Prehypertensive subjects have greater risk of developing hypertension than the normotensive subjects. Studies have shown that lipid profile is altered in hypertensive patients as compare to normotensive subjects. But not much is documented about lipid profile in prehypertensives. So the present study is done to compare the serum lipid profile among prehypertensive and normotensives and to correlate the blood pressure and lipid profile in prehypertensives. Methods: 50 prehypertensive and 50 normoten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…While the maximum number of prehypertensive in a study conducted by Hitesh A. Jani et al was found to be 2nd to 3rd decade. [16] This present study shows the mean SBP and DBP of prehypertensives group were higher than those of normotensives group, which is much similar to that reported by Hitesh A Jani et al who observed that SBP & DBP in hypertensives. [16] …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…While the maximum number of prehypertensive in a study conducted by Hitesh A. Jani et al was found to be 2nd to 3rd decade. [16] This present study shows the mean SBP and DBP of prehypertensives group were higher than those of normotensives group, which is much similar to that reported by Hitesh A Jani et al who observed that SBP & DBP in hypertensives. [16] …”
Section: Resultssupporting
confidence: 91%
“…[ [16,17] From the present study we have found an association of dyslipidemia with prehypertension. A population study in china in 1154 subjects found that total cholesterol, LDL, VLDL, Triglyceride were significantly increased & HDL were significantly decreased in prehypertensives.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation